2019
DOI: 10.1177/0969733019889396
|View full text |Cite
|
Sign up to set email alerts
|

Professional values and ethical ideology: Perceptions of nursing students

Abstract: Background: Moral philosophical positions and professional values have been shown to influence nurses’ practice behaviours. Understanding nursing students’ professional values and ethical ideologies, therefore, is important as they may help inform evidence-informed curriculum decisions and education strategies to develop students’ professional reflective competencies. However, there is a dearth in current empirical data on Canadian nursing students’ perceptions of professional values and ethical positions. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
5
23
1
1
Order By: Relevance
“…In nursing students, ethical ideology is associated with professional values (Arries, 2019) self-identified culture, and intrinsic religiosity (White et al, 2019). In their study, White et al (2019) found that students whose parents were not born in the United States scored higher on ethical idealism.…”
Section: Overview Of Literature On Moral Philosophy and Ethical Ideol...mentioning
confidence: 97%
See 1 more Smart Citation
“…In nursing students, ethical ideology is associated with professional values (Arries, 2019) self-identified culture, and intrinsic religiosity (White et al, 2019). In their study, White et al (2019) found that students whose parents were not born in the United States scored higher on ethical idealism.…”
Section: Overview Of Literature On Moral Philosophy and Ethical Ideol...mentioning
confidence: 97%
“…In nursing students, ethical ideology is associated with professional values (Arries, 2019) self-identified culture, and intrinsic religiosity (White et al., 2019). In their study, White et al.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Tehranineshat, Torabizadeh & Bijani (2020) concluded that increasing knowledge regard nurses' professional values and ethical climate at work environment can assist nursing managers to determine suitable strategies to increase satisfaction and decrease burnout and work stress. Arries (2020) emphasized that professional values affect nurses' behaviors. Therefore, it may provide evidenced information for curriculum improvement and effective educational strategies to expand students' clinical and professional competencies.…”
Section: Significancementioning
confidence: 99%
“…Professional values are the framework and standard for the conduct of professionals. Any professional group has its professional values [ 1 ]. As the largest medical care group, nurses’ professional values are particularly critical, which form the basis of nursing practice and the standard for nurses to interact with patients and colleagues [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%